Positive effects of spirituality in facilitating recovery for people with severe mental illness - Dr. , Daniel Young (International Journal of Psychosocial Rehabilitation, 2015)
This study aims at exploring positive impacts of spirituality on helping people with severe mental illness to overcome loss and despair in recovery. In-depth semi-structured interviews were conducted with six Chinese people having severe mental illness who relied on spir- ituality to facilitate their recovery. Five themes of spirituality are identified helping individuals to overcome profound loss and despair in recovery, including: positive meaning towards mental illness; hope for recovery; forgiveness; social support, and spiritual coping. Spirituality is found to have positive effects on mental health recovery. Benefits of spiritual interventions, e.g. forgiveness therapy, on mental health recovery worthwhile further study.